Pre-existing Corneal Astigmatism in patients undergoing Cataract Surgery in Western Nepal; A hospital-based Unicentered, Comprehensive, Prospective Observational Study - Shrestha, Shristi; Kaini, Khemraj (Nepal Journal of Medical Sciences, 2020)
Introduction: Cataract surgery is one of the most commonly performed surgical procedures worldwide. The final postoperative visual acuity is dependent on the pre-existing corneal astigmatism, accurate biometry and surgically induced astigmatism. Because of the increase in the patient’s demand for better postoperative visual acuity, it becomes important to evaluate the distribution of pre-existing corneal astigmatism in different populations. The objective of the study was to analyze the magnitude and pattern of pre-existing corneal astigmatism in cataract surgery patients in Western Nepal. Methods: A hospital-based cross-sectional descriptive study was carried out in the Department of Ophthalmology, Manipal Teaching Hospital, Pokhara. Three hundred and two patients undergoing routine cataract surgery between February 2016 and January 2018 were recruited in the study. Keratometric data from these patients were collected and were analyzed using the statistical software SPSS version 21. Results: The mean age of the subjects was 70.25 ± 10.97 years (range 35 to 94 years). There was a preponderance of females (62%) over males (38%). The mean corneal astigmatism was 0.78 ± 0.59 D (range 0.00 to 5.00 D). The pre-existing corneal cylinder ≥ 1.00 D was seen in 40.06% of patients. The corneal astigmatism was mainly against the rule (65.56%). The amount of corneal astigmatism and corneal steepness increased with age. Conclusion: Corneal astigmatism of 1.00 D or more was seen in 40.06% of the patients undergoing cataract surgery which should be corrected to meet the patient’s expectation for good, unaided visual acuity after cataract surgery.